Activity of Origanum vulgare Essential Oil in Liquid and Vapor Phase against Pathogenic Microorganisms - Lucia Galovičová; Petra Borotová; Hana Ďúranová; Veronika Valková; Miroslava Kačániová (Scientific Papers Animal Science and Biotechnologies, 2023)
The analysis was aimed to evaluate the antimicrobial activity of the essential oil Origanum vulgare against various gram-positive and gram-negative bacteria and yeast. To test its suitability in the vapor phase for the elimination of biofilm-forming bacteria on fruits and vegetables. To evaluate its potential for use in the storage of vegetables and fruits. The tested essential oil Origanum vulgare showed strong antimicrobial activity against various types of microorganisms. Due to the high antimicrobial activity against diverse group of microorganisms, it could also be a suitable option for the post-harvest treatment of crops in the future. In evaluating the inhibitory activity in the vapor phase, an effect on the biofilm-forming bacteria S. maltophilia and B. subtilis was demonstrated. Against S. maltophilia, the highest efficacy was found at a concentration of 500 µL/L by 91.27% inhibition of bacteria on potatoes. Against B. subtilis, the most effective concentration was 250 µL/L by 63.24 % of bacterial inhibition on carrots. Relatively stable growth inhibition was found in the apple sample at all concentrations tested. Due to the vaporous application, it would be possible to use lower concentrations of essential oils to achieve the antimicrobial activity. The impact on the sensory properties of food would be reduced.